Pengaruh Brand Trust dan Brand Experience Terhadap Brand Loyalty pada Wardah Cosmetic di Kota Malang - Fatimah Zahrotul Aminah; Achmad Zaini; Asminah Rachmi (PENG: Jurnal Ekonomi dan Manajemen, 2026)
cosmetics industry in Indonesia is experiencing rapid growth along with the increasing trend of facial care for both women and men. Wardah Cosmetic as a local halal brand competes with local and global brands amidst a tight market, but still faces challenges in maintaining consistent brand loyalty. This study aims to analyze the influence of brand trust and brand experience on Wardah Cosmetic brand loyalty in Malang City. A quantitative approach was used involving 100 respondents selected through purposive sampling, with the criteria of having used Wardah products at least twice and shopping at the Wardah Official Store Malang. Data were collected through questionnaires and analyzed using questionnaire tests, descriptive analysis, classical assumption tests, multiple linear regression, coefficient of determination, and hypothesis tests. The results of partial tests indicate that brand trust has a negative effect on brand loyalty, while brand experience has a positive effect. Simultaneous tests show that both variables have a significant effect on brand loyalty. These findings confirm that brand experience has a dominant role in building loyalty, while brand trust needs to be strengthened through differentiation and expansion of the brand experience. Wardah is advised to optimize its experience-based marketing strategy and improve communication regarding product advantages to build long-term loyalty.